Hsp90 Inhibition Protects Against Biomechanically Induced Osteoarthritis in Rats. Issue 8 (26th July 2013) - Siebelt, Michiel; Jahr, Holger; Groen, Harald C.; Sandker, Marjan; Waarsing, Jan H.; Kops, Nicole; Müller, Cristina; van Eden, Willem; de Jong, Marion; Weinans, Harrie
Abstract : Objective: Although articular cartilage has evolved to facilitate joint mobilization, severe loading can induce chondrocyte apoptosis, which is related to the progression of osteoarthritis (OA). To avoid apoptosis, chondrocytes synthesize heat‐shock proteins (HSPs). This study was undertaken to examine the roles of Hsp70 and Hsp90 in biomechanically induced OA, and the possibility of using Hsp90 inhibition as an intervention strategy for OA management. Methods: OA was biomechanically induced in rats by means of strenuous running. Disease progression was compared between running rats treated with Hsp90 inhibitor and untreated running controls. Hsp70 and Hsp90 protein levels in articular cartilage were determined by Western blotting. OA progression was monitored using contrast‐enhanced micro–computed tomography to measure cartilage degradation and subchondral bone changes and single‐photon–emission computed tomography to examine synovial macrophage activation and histologic features. Results: Chronic cartilage loading led to early OA development, characterized by degeneration of cartilage extracellular matrix. In vivo Hsp90 inhibition resulted in increased Hsp70 synthesis, which suggests that Hsp90 activity limits Hsp70 production. Hsp90 inhibitor treatment increased cartilage sulfated glycosaminoglycan levels to concentrations even beyond baseline and protected against cartilage degradation, stimulated subchondral bone thickness, and suppressed macrophage activation. Conclusion: Our findings indicate that Hsp90 plays a pivotal role in biomechanically induced chondrocyte stress responses. Intervention strategies that inhibit Hsp90 can potentially protect or improve cartilage health and might prevent OA development.